Synthesis and applications of transition metal dichalcogenide-based nanomaterials - Shi, Zhenyu (Nanyang Technological University, 2021)
Great advancement has been achieved in two-dimensional (2D) materials which greatly accelerated the research in 2D transition metal dichalcogenides (TMDs) nanomaterials owing to their diverse chemical compositions, atomic structures and unique properties. One of the most important features of 2D TMDs nanomaterials is that they can exist in different polymorphisms with various electronic properties. For example, Group-VI TMDs nanosheets (NSs), such as MoS2 and MoSe2, exhibit the thermodynamically stable 2H-phase, which is semiconducting, and the metastable 1T or 1T′ phase, which is metallic or semi-metallic. However, due to the metastable nature, the preparation of Group-VI TMDs nanosheets with 1T or 1T′ phase is still required further investigation, thus their intrinsic properties remain unclear. Only the TMDs NSs with mixed phases, i.e., 2H, 1T and 1T′ phases mixed together, can be obtained by using the traditional methods, such as lithium intercalation, hydrothermal or solvothermal methods. Therefore, it is highly desired to develop a facile, controllable method towards the preparation of 1T- or 1T′-TMDs NSs with high phase purity to in-depth study their properties and applications. First, we reported an electrochemical intercalation and exfoliation method that successfully prepared a variety of metastable 1T′-TMDs materials such as 1T′-MoS2, 1T′-MoSe2 and 1T′-MoSSe NSs with high quality, high yields, and high phase purity. The as-prepared high purity 1T′-MoS2 NSs exhibited enhanced hydrogen evolution reaction (HER) activity as compared with the 2H counterpart, which is prepared by using the same method. The electrochemical intercalation and exfoliation method can also be extended to exfoliate other layered materials, showing great generality. Second, the high phase purity 1T′-MoS2 and 2H-MoS2 NSs serve as ideal platforms for the growth of secondary nanomaterials, which enables us to fabricate novel MoS2-based hybrids nanomaterials and investigate the crystal phase-dependent properties. Here we reported the preparation of Pt/1T′-MoS2 and Pt/2H-MoS2 hybrid nanomaterials, in which the Pt nanostructures exhibit distinct electronic properties. The Pt/1T′-MoS2 shows excellent HER activity and stability. At the overpotential of only 10 mV, Pt/1T′-MoS2 can reach a current density of 10 mA cm-2, which is dramatically lower than the Pt/2H-MoS2 (reaching 10 mA cm-2 at the overpotential of 113 mV) and even the commercial Pt/C catalyst (reaching 10 mA cm-2 at the overpotential of 19 mV). The superior catalytic performance of Pt/1T′-MoS2 highlights the significance of the crystal phase for structure and property tailoring towards promising applications.